Vocational Education for Indian Youth with Special Needs in Dubai: Evaluating the Availability and Quality - Bamji, Gulnar (2016)
The dissertation researches the availability and offerings of vocational education to 14-25 year old Indian youth with Special Needs in Dubai, UAE. The study investigates if the provision and quality of institutes and curriculum imparted makes the Indian youth economically independent and socially inclusive. Using mixed method approach, the research explores the challenges in the areas of fees, the mismatch between the taught syllabus and the industry requirements, the lack of tools for an enhanced social, emotional and behavioral skills among others. The findings lead to relevant suggestions for further improvement in the sector.